Multiple sensory illusions are evoked during the course of proton therapy. (August 2020) - Narici, Livio; Titova, Elena; Obenaus, André; Wroe, Andrew; Loredo, Lilia; Schulte, Reinhard; Slater, Jerry D.; Nelson, Gregory A.
Abstract: Visual illusions from astronauts in space have been reported to be associated with the passage of high energy charged particles through visual structures (retina, optic nerve, brain). Similar effects have also been reported by patients under proton and heavy ion therapies. This prompted us to investigate whether protons at the Loma Linda University Proton Therapy and Research Center (PTRC) may also affect other sensory systems beside evoking similar perceptions on the visual system. A retrospective review of proton radiotherapy patient records at PTRC identified 29 sensory reports from 19 patients who spontaneously reported visual, olfactory, auditory and gustatory illusions during treatment. Our results suggest that protons can evoke neuronal responses sufficient to elicit conscious sensory illusion experiences, in four senses (auditory, taste, smell, and visual) analogous to those from normal sensory inputs. The regions of the brain receiving the highest doses corresponded with the anatomical structures associated with each type of illusion. Our findings suggest that more detailed queries about sensory illusions during proton therapy are warranted, possibly integrated with quantitative effect descriptions (such as electroencephalography) and can provide additional physiological basis for understanding the effects of protons on central nervous system tissues, needed for radiation risk assessment in advance of deep space human exploration.